Neurologic Abnormalities in Williams Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
The neurologic features of 47 cases of Williams syndrome were determined and a follow-up study was performed on a subgroup of 27 subjects at the Neurorehabilitation Unit, IRCCS Eugenio Medea, Bosisio Parini, Italy.